2017
DOI: 10.1210/en.2017-00027
|View full text |Cite
|
Sign up to set email alerts
|

Incretin Therapies Do Not Expand β-Cell Mass or Alter Pancreatic Histology in Young Male Mice

Abstract: The impact of incretins upon pancreatic β-cell expansion remains extremely controversial. Multiple studies indicate that incretin-based therapies can increase β-cell proliferation, and incretins have been hypothesized to expand β-cell mass. However, disagreement exists on whether incretins increase β-cell mass. Moreover, some reports indicate that incretins may cause metaplastic changes in pancreatic histology. To resolve these questions, we treated a large cohort of mice with incretin-based therapies and carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Many studies have shown GLP-1R agonists and DPP-4 inhibitors have mitogenic effects on β cells in rodents [ 35 37 ], but some showed otherwise. For instance, a newly published study using a large cohort of young male mice has shown that incretin (exenatide and sitagliptin) therapies have little impact on β -cell proliferation and mass expansion following long-term (4.5 months) treatment [ 38 ], although the authors indeed have observed moderate β -cell proliferation following short-term (2 weeks) treatment. Together, these studies suggest that the mitogenic potential of incretin therapies may be affected by drug dosage, administration route, treatment duration, and the nature of diabetes models [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown GLP-1R agonists and DPP-4 inhibitors have mitogenic effects on β cells in rodents [ 35 37 ], but some showed otherwise. For instance, a newly published study using a large cohort of young male mice has shown that incretin (exenatide and sitagliptin) therapies have little impact on β -cell proliferation and mass expansion following long-term (4.5 months) treatment [ 38 ], although the authors indeed have observed moderate β -cell proliferation following short-term (2 weeks) treatment. Together, these studies suggest that the mitogenic potential of incretin therapies may be affected by drug dosage, administration route, treatment duration, and the nature of diabetes models [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…57 In fact, in our study GLP-1 did not influence ki-67 staining in β-cell, similar to what was reported in more recent studies. 58 Conversely, chronic GLP-1 exposure, resulted in a lower ki-67 stained α-cells in rats with intact vagal pathway than in vagotomized rats. GLP-1R are present in α-cells 59 and have an active role in glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from a different group showed that the addition of a dipeptidyl peptidase-IV (DPP-IV) inhibitor, TS-021, with metformin treatment had the opposite effect, increasing ␤-cell mass and lowering glucose, although ␤-cell proliferation directly was not examined (81). Furthermore, the incretin-effect of DPP-IV inhibition on mouse ␤-cell mass expansion following HFD feeding has not been validated by other studies (21). Similarly, although in an entirely different class of drugs, ␤-hydroxy-␤-methylglutaryl (HMG)-CoA reductase inhibitors (statins), which act by lowering endogenous cholesterol synthesis in the liver, have been linked with a 9% increased risk of Type 2 diabetes, particularly in older patients (73).…”
Section: Discussionmentioning
confidence: 99%